My mixed emotions : help your kids handle their feelings - Greenwood, Elinor (DK Publishing, 2018)
Feelings can be complicated, and learning to express them is a skill that must be developed. My Mixed Emotions is here to coach children through a variety of emotions and situations including dealing with bullying, understanding grief, and coping with large family changes, such as divorce. Divided into happiness, fear, anger, and sadness, My Mixed Emotions explores the four main emotions, the reasons why we feel them, and the science behind each one. Children will discover great things about themselves, such as what happens in their brain when they are happy, why they cry when they are sad, and why they sometimes feel nervous. -- Provided by publisher.